Pengembangan Ensiklopedia Tumbuhan Obat Masyarakat Kerinci Sebagai Sumber Belajar Materi Keanekaragaman Hayati Untuk Siswa SMA: (Development of Encyclopedia of Medicinal Plants for the Kerinci Community as Learning Resources for Biodiversity Materials for High School Students) - Reni Julianti; Revis Asra; Upik Yelianti (BIODIK, 2021)
The abundant population of plant species in Kerinci district is utilized by the community for daily needs, including using plants as medicine to cure various diseases. To help increase public knowledge, especially students, about medicinal plants, one of them is by integrating into Biology learning in Biodiversity material. This research is a development research. The development model in this study is the ADDIE model. The ADDIE model consists of 5 stages, namely analysis, design, development, implementation and evaluation. The products of the Kerinci Community Medicinal Plant Encyclopedia were previously tested and validated by a team of experts, namely material experts and media experts to determine the feasibility of the products being made. The Kerinci Community Medicinal Plant Encyclopedia was validated by media experts with a very good score of 94.4% and material experts with a score of 95.46% in the very good category. Thus the encyclopedia product is said to be feasible. This product was then tested at SMAN 2 Kerinci, the trial was carried out on 2 biology subject teachers, a small group consisting of 9 students, in a large group consisting of 34 students. The test results on the teacher obtained a score of 99.2%. The test results in the small group obtained a score of 94.96% which was in the very good category. In the large group trial obtained a score of 96.44% including the very good category. Thus the product of the Kerinci Community Medicinal Plants encyclopedia is suitable for use as a learning resource. The effectiveness test of using the Kerinci Community Medicinal Plant encyclopedia is effective for improving student learning outcomes. Abstrak. Melimpahnya populasi jenis tumbuhan yang ada di kabupaten Kerinci dimanfaatkan masyarakat untuk keperluan sehari-hari, diantaranya memanfaatkan tumbuhan sebagai obat untuk menyembuhkan berbagai penyakit. Untuk membantu meningkatkan pengetahuan masyarakat khususnya para peserta didik terhadap tumbuhan obat salah satunya dengan mengintegrasikan kedalam pembelajaran Biologi pada materi Keanekaragaman Hayati. Penelitian ini merupakan penelitian pengembangan. Model pengembangan dalam penelitian ini adalah model ADDIE. Model ADDIE terdiri dari 5 tahap yaitu analysis, design, development, implementation dan evaluation. Produk Ensiklopedia Tumbuhan Obat masyarakat Kerinci sebelumnya diujicobakan terlebih dahulu divalidasi oleh tim ahli yaitu ahli materi dan ahli media untuk mengetahui kelayakan dari produk yang dibuat. Ensiklopedia Tumbuhan Obat Masyarakat Kerinci divalidasi oleh ahli media dengan perolehan skor 94,4% kategori sangat baik dan ahli materi dengan skor 95,46% kategori sangat baik. Dengan demikian produk ensiklopedia dikatakan layak. Produk ini kemudian diujicobakan di SMAN 2 Kerinci, uji coba dilakukan pada 2 orang guru mata pelajaran biologi, kelompok kecil terdiri dari 9 orang siswa, pada kelompok besar terdiri dari 34 orang siswa. Hasil uji coba pada guru memperoleh skor 99,2% hasil uji coba pada kelompok kecil memperoleh skor 94,96% yang termasuk kategori sangat baik. Pada uji coba kelompok besar memperoleh skor 96,44% termasuk kategori sangat baik. Dengan demikian produk ensiklopedia Tumbuhan Obat Masyarakat Kerinci ini layak digunakan sebagai sumber belajar. Uji efektifitas penggunaan ensiklopedia Tumbuhan Obat Masyarakat Kerinci efektif untuk meningkatkan hasil belajar siswa.Â